IMPROVING STUDENTS’ WRITING DESCRIPTIVE ENGLISH TEXT IN MULTILITERATION LEARNING THROUGH COLLABORATIVE TECHNIQUES - Mayasari, Santi; Firdaus, Masagus; Widayatsih, Tri (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2018)
Abstract: The purpose of this study is to improve students' writing skills in Multiliteration Learning English descriptive text through collaboration techniques in Seniour high school students in Palembang. This study used a Quasi-experimental research design method; non equivalent pretest and posttest. In analyzing the level of writing comprehension of students by using the rubric of writing descriptive text, the final test scores of control class students and experimental class students were be compared. Then the t-test value was compared with the value of t-table. The results obtained, by looking at Table t-test results, it was found that the F value is 110.049 with degreef of freedom (df) 292 with a significance value (sig.) 0,000. With the difference in the mean value of 4.116. Due to the sig value. 0,000 (<0,005) with a t-count value was 8.540, it can be concluded that there are significant differences between the two sample groups in the final results of writing skills. It can be concluded that collaboration techniques have a positive impact on students' writing abilities. Keywords:  multiliteration, collaboration, descriptive text